2019
DOI: 10.1186/s13000-019-0894-1
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 3113-5p is a novel marker for early cardiac ischemia/reperfusion injury

Abstract: BackgroundIschemia/reperfusion (I/R) injury of heart is one of the major causes of acute cardiac injury, which may result in worsening or even loss of heart function. With novel microRNAs being evolutionarily discovered, numbers of them remained functionally unknown. We aimed to discover novel microRNAs with therapeutic or diagnostic potential in the setting of early cardiac I/R injury.MethodsCardiac electrical activity, biochemical detection and histopathology analysis were performed to reveal early changes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…We thus assessed whether four cardio-miRNAs (miR-3113-5p, miR-223-3p, miR-499a-5p, and miR-133a-3p) had any diagnostic values. The selection of these miRNAs was based on published literature [ 28 , 30 , 31 ] and our previous work [ 26 ] . Our aims were two-fold: one to assess whether these miRNAs could diagnose SCD, and the other one to assess whether specific miRNAs had higher efficacy as to discriminate the causes of SCD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We thus assessed whether four cardio-miRNAs (miR-3113-5p, miR-223-3p, miR-499a-5p, and miR-133a-3p) had any diagnostic values. The selection of these miRNAs was based on published literature [ 28 , 30 , 31 ] and our previous work [ 26 ] . Our aims were two-fold: one to assess whether these miRNAs could diagnose SCD, and the other one to assess whether specific miRNAs had higher efficacy as to discriminate the causes of SCD.…”
Section: Resultsmentioning
confidence: 99%
“…miR-223 was upregulated in a rat model of AMI and its overexpression promoted cardiac arrhythmias [ 23 ]; thus, miR-223 may be a new target in the treatment of ischemic arrhythmias. Our previous research showed that cardiac miR-3113-5p might be a useful target for therapeutic purposes and circulating miR-3113-5p might serve as a stable marker for early diagnosis of cardiac ischemia-reperfusion injury [ 26 ]. miR-499-5p is highly conserved and preferentially expressed in the myocardium [ 41 ]; circulating levels of miR-499-5p were significantly higher at admission in AMI patients that died within the following year as compared to those who survived the cardiovascular event [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-223 was upregulated in a rat model of AMI and its overexpression promoted cardiac arrhythmias [26]; thus, miR-223 may be a new target in the treatment of ischemic arrhythmias. Our previous research showed that cardiac miR-3113-5p might be a useful target for therapeutic purposes and circulating miR-3113-5p might serve as a stable marker for early diagnosis of cardiac ischemiareperfusion injury [33]. miR-499-5p is highly conserved and preferentially expressed in the myocardium [44], circulating levels of miR-499-5p were signi cantly higher at admission in AMI patients that died within the following year as compared to those that survived the cardiovascular event [45].…”
Section: Discussionmentioning
confidence: 99%
“…We thus assessed whether four cardio-miRNAs (miR-3113-5p, miR-223-3p, miR-499a-5p, and miR-133a-3p) had any diagnostic values. The selection of these miRNAs was based on published literature [30][31][32] and our previous work [33] . Our aims were two-fold: one to assess whether these miRNAs could diagnose SCD, and the other one to assess whether speci c miRNAs had higher e cacy as to discriminate the causes of SCD.…”
Section: Common Molecular Markers Failed To Discriminate the Scd Cases Categorized As Ami From Control Casesmentioning
confidence: 99%